The Schools of Arts and Crafts of New Spain as predecessors of current technical professional education - Elena Zhizhko; Gali Aleksandra Beltrán; Martín Beltrán Saucedo (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
In this article we present the results of the historical-pedagogical research, which objective was to establish the premises for the development of the novohispanic Schools of Arts and Crafts as predecessors of current Mexican technical professional education, through a documentary-bibliographic study. Th e authors found, that the prerequisites of the appearance of the Mexican technical professional education system were created since the 16th century, and the novohispanic Schools of Arts and Crafts were the grounds for its development. In addition, the premises for the development of the novohispanic Schools of Arts and Crafts were the introduction of new agricultural, textiles, construction, and mining extraction technologies to the new continent by the Spanish, and the request for Amerindian peoples' instruction for its use. Th is teaching was provided by the conquistadors along with the evangelization and Castilianization of the natives in the Schools of Arts and Crafts. Later, in the 18th - early 19th centuries, there were opened the new Schools of Arts and Crafts (the schools for workers) of engraving, painting, mining, spinning, weaving, etc. - the direct predecessors of the current technical professional schools.  Szkoły Sztuki i Rzemiosła Nowej Hiszpanii jako poprzedniczki współczesnego technicznego kształcenia zawodowego W artykule prezentujemy wyniki badań historyczno-pedagogicznych, których celem było ustalenie przesłanek rozwoju nowohiszpańskich szkół artystycznych i rzemieślniczych jako poprzedników obecnego meksykańskiego technicznego kształcenia zawodowego, poprzez analizę treści. Autorzy ustalili, że fundamenty meksykańskiego systemu technicznego kształcenia zawodowego powstawały już w XVI w., a podstawą jego rozwoju były nowohiszpańskie Szkoły Sztuki i Rzemiosła. Ponadto przesłanką do rozwoju nowohiszpańskich szkół artystycznych i rzemieślniczych było wprowadzenie przez Hiszpanów na nowy kontynent nowych technologii rolniczych, tekstylnych, budowlanych, wydobywczych i prośba o instruktaż ludów indiańskich w zakresie ich stosowania. Nauczanie to zapewniło konkwistadorom ewangelizację i kastylizację tubylców w szkołach artystycznych i rzemieślniczych. Później, w XVIII - na  początku XIX w., otwarto nowe Szkoły Rzemieślnicze (szkoły robotnicze): rytownicze, malarskie, górnicze, przędzalnicze, tkackie itp., bezpośrednie poprzedniczki obecnych technicznych szkół zawodowych.